Fontan‐associated plastic bronchitis waitlist and heart transplant outcomes: A PHTS analysis. (6th January 2021) - Bearl, David W.; Cantor, Ryan; Koehl, Devin; Gossett, Jeffrey G.; Bock, Matthew J.; Halnon, Nancy; Glass, Lauren; Exil, Vernat; Musselwhite, Courtney; Kirklin, James K.; Godown, Justin; Ravishankar, Chitra
Abstract: Plastic bronchitis is a rare post‐Fontan complication with limited treatment options. Heart transplantation has evolved as a potential curative option, but outcomes have not been well‐defined. This study aims to assess contemporary waitlist and post‐transplant outcomes in patients with plastic bronchitis. All Fontan patients were identified in the PHTS database (2010 ‐ 2018). Waitlist and post‐transplant outcomes were compared between Fontan patients with and without plastic bronchitis. Competing outcomes and Kaplan‐Meier analyses were used to assess the impact of plastic bronchitis on waitlist and post‐transplant survival. A secondary analysis excluded those with PLE from the comparison cohort. Of 645 Fontan patients listed for heart transplant, 69 (11%) had plastic bronchitis. At listing, patients with plastic bronchitis were younger (8.9 vs 11.1 years, P = .02), but had few other differences in baseline characteristics. A fewer Fontan patients with plastic bronchitis were listed in the more recent era (46 [15.4%] in 2010‐2014 vs 23 [6.6%] in 2015‐2018, P < .01). Overall, there was no difference in waitlist ( P = .30) or post‐transplant ( P = .66) survival for Fontan patients with and without plastic bronchitis. The results were similar after excluding patients with PLE. Contrary to prior reports, this relatively large series showed that plastic bronchitis did not have a negative impact on survival to or after heart transplantation in Fontan patients. Our study also found a 50% reduction in listing in the current era, which may indicate evolution in management of Fontan patients.